Both Nuclear Size and DNA Amount Contribute to Midblastula Transition Timing in Xenopus laevis - Predrag Jevtić (Nature Portfolio, 2017)
Abstract During early Xenopus laevis embryogenesis both nuclear and cell volumes decrease with the nuclear-to-cytoplasmic (N/C) volume ratio reaching a maximum at the midblastula transition (MBT). At the MBT, embryonic transcription is upregulated and cell cycles lengthen. Early studies demonstrated a role for the DNA-to-cytoplasmic ratio in the control of MBT timing. By altering nuclear size, we previously showed that the N/C volume ratio also contributes to proper MBT timing. Here we examine the relative contributions of nuclear size and DNA amount to MBT timing by simultaneously altering nuclear size and ploidy in X. laevis embryos. Compared to diploid embryos, haploids exhibited a delay in both zygotic gene expression and cell cycle lengthening, while diploid embryos with increased N/C volume ratios showed early expression of zygotic genes and premature lengthening of cell cycles. Interestingly, haploids with increased N/C volume ratios exhibited an intermediate effect on the timing of zygotic gene expression and cell cycle lengthening. Decreasing nuclear size in post-MBT haploid embryos caused a further delay in cell cycle lengthening and the expression of some zygotic genes. Our data suggest that both the N/C volume ratio and DNA amount contribute to the regulation of MBT timing with neither parameter being dominant.